Tissue block-resolved developmental transcriptomic atlas of human fetal brainstem reveals gene modules with implications for neurological disorders - Liu, Chengxin; Zhou, Wenjuan; Xing, Xin; Chen, Jiachen; Sun, Chenxi; Liu, Shizhou; Lou, Yunxia; Jiao, Jianfen; Cao, Haoling; Cui, Baoxia; Hong, Shuhui; Ahmadi, Niloufar; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThe brainstem is a critical hub connecting the cerebrum and spinal cord. However, the gene regulatory dynamics during fetal brainstem development remain incompletely characterized.MethodsThis study employed RNA-seq to map transcriptomes across 107 tissue blocks from 18 human fetal brainstems (gestational weeks 9–33). Weighted gene co-expression network analysis (WGCNA) identified 22 functionally annotated modules. We quantitatively assessed their spatiotemporal activity gradients and systematically classified genes exhibiting significant temporal trajectories based on phase-specific signatures.ResultsOur integrated approach constructed a developmental transcriptomic profile, revealing stage-specific regulatory networks and dynamic transcriptional trajectories governing ontogeny. Crucially, we validated the expression of neurodevelopmental disorder-associated genes within fetal brainstem tissues.DiscussionThis work advances our understanding of brainstem development and provides a foundational resource for research into neurological disorders.